Co-Overexpression of RIB1 and RIB6 Increases Riboflavin Production in the Yeast Candida famata - Yana Petrovska; Oleksii Lyzak; Justyna Ruchala; Kostyantyn Dmytruk; Andriy Sibirny (Fermentation, 2022)
Riboflavin or vitamin B2 is a water-soluble vitamin and a precursor of flavin coenzymes, flavin mononucleotide, and flavin adenine dinucleotide, which play a key role as enzyme cofactors in energy metabolism. Candida famata yeast is a promising producer of riboflavin, as it belongs to the group of so-called flavinogenic yeasts, capable of riboflavin oversynthesis under conditions of iron starvation. The role of the particular structural genes in the limitation of riboflavin oversynthesis is not known. To study the impact of overexpression of the structural genes of riboflavin synthesis on riboflavin production, a set of plasmids containing genes RIB1, RIB6, and RIB7 in different combinations was constructed. The transformants of the wild-type strain of C. famata, as well as riboflavin overproducer, were obtained, and the synthesis of riboflavin was studied. It was found that overexpression of RIB1 and RIB6 genes coding for enzymes GTP cyclohydrolase II and 3,4-dihydroxy-2-butanone-4-phosphate synthase, which catalase the initial steps of riboflavin synthesis, elevated riboflavin production by 13–28% relative to the parental riboflavin-overproducing strains.